The effect of surgically assisted rapid maxillary expansion on sleep architecture: an exploratory risk study in healthy young adults. (21st October 2013) - Bach, N.; Tuomilehto, H.; Gauthier, C.; Papadakis, A.; Remise, C.; Lavigne, F.; Lavigne, G. J.; Huynh, N.
Summary: Maxillary transverse deficiencies (MTD) cause malocclusions. Rapid maxillary expansion treatment is commonly used treatment for correcting such deficiencies and has been found to be effective in improving respiration and sleep architecture in children with obstructive sleep apnoea (OSA). However, thus far, the effect of surgically assisted rapid maxillary expansion (SARME) treatment on sleep architecture and breathing of normal subjects has not been assessed. We hypothesised that sleep quality will improve after maxillary expansion treatment. The objective of this study is to access the effect of maxillary expansion treatment on sleep structure and respiratory functions in healthy young adults with severe MTD. This is a prospective and exploratory clinical study. Twenty‐eight consecutive young adult patients (15 males and 13 females, mean age 20·6 ± 5·8 years) presenting with severe MTD at the orthodontic examination were recruited into the study. All the participants underwent a standardised SARME procedure (mean expansion 6·5 ± 1·8 and 8·2 ± 1·8 mm, intercanine and intermolar distance, respectively) to correct malocclusion caused by MTD. An overnight in‐laboratory polysomnography, before and after the treatment, was performed. The mean follow‐up time was 9 months. The main outcome parameters were the changes in sleep architecture, including sleep stages, arousals, slow‐wave activity (SWA) and respiratory variables. Before surgery, young adult patients with MTD presented no evidence of sleep breathing problems. At baseline sleep recording, 7 of 28 (25%) had apnoea‐hypopnoea index (AHI) ≥ 5 events per hour. No negative effect of the SARME was observed in questionnaires or sleep laboratory parameters. In the patients with a higher baseline AHI (AHI ≥ 5 h of sleep), we observed a reduction in AHI after surgical treatment ( P = 0·028). SARME did not have a negative effect on any sleep or respiration parameters in healthy young individuals with MTD. It normalised the breathing index in the patients with a mild AHI index.